158 The Anti-Platelet Effectiveness of P2Y12 Receptor Blockade is Strongly Influenced by the Endothelium-Derived Mediators Nitric Oxide and Prostacyclin. (6th June 2015) - Knowles, Rebecca; Chan, Melissa; Hayman, Melissa; Armstrong, Paul; Tucker, Arthur; Timmis, Adam; Warner, Timothy
Abstract : Introduction: P2Y12 receptor antagonists that block the pro-aggregatory effects of ADP on platelets are commonly prescribed alongside aspirin, as dual antiplatelet therapy (DAPT) for secondary prevention of atherothrombotic events. It is emerging that these agents exert part of their effects through potentiation of the endogenous, endothelial-derived platelet inhibitors, nitric oxide (NO) and prostacyclin (PGI2 ), which constantly bathe circulating platelets reducing their reactivity through elevating levels of cyclic nucleotides. Thus, if the in vivo synergy between NO and PGI2 amplifies the anti-thrombotic effects of P2Y12 inhibitors, within the circulation variances in the levels of endothelial-derived mediators will be an important determinant of the efficacy of DAPT, suggesting that for the individual patient, endothelial function influences the therapeutic potential of these powerful agents. Here, we characterised the interplay of PGI2, NO and P2Y12 blockade on platelet function. Methods: 8 healthy male volunteers received aspirin (75 mg) and prasugrel (10 mg) for 7 days. Platelet responses to TRAP-6 (25 ìM) or collagen (4 ìg/ml) in the presence of PGI2 (1 nM), NO (100 nM), PGI2 +NO or vehicle were assessed by LTA and lumi-aggreggometry. Experiments were replicated in vitro (n = 4) utilising aspirin (30 ìM) and prasugrel active metabolite (PAM; 6, 3 or 1.5 ìM) representing maximal and partial P2Y12 blockade. Results: Ex vivo, prior to DAPT, PGI2, NO, or PGI2 +NO had little effect upon platelet aggregation. TRAP-6 (25 ìM): vehicle, 74 ± 3%; PGI2 +NO, 66 ± 3%. Following DAPT, PGI2 or NO alone caused minor inhibition: vehicle, 57 ± 4%; PGI2, 47 ± 6%; NO 49 ± 6%. Conversely, the combination of PGI2 +NO produced strong inhibitory effects, 19 ± 6% (p < 0.05). Lumi-aggregometry quantifying ADP+ATP, showed dense granule release was unaffected in individuals receiving DAPT (7.5 ± 1.7 to 7.7 ± 0.6 nmole) but was reduced with addition of DEA/NONOate+PGI2 (6.3 ± 1.9 to 3.7 ± 1.3 nmole, p < 0.05). In vitro, with maximal P2Y12 inhibition (PAM, 6 ìM) aggregation to TRAP-6 (25 ìM) was reduced: vehicle, 56 ± 5%; PGI2, 30 ± 12%; NO, 46 ± 7%; PGI2 +NO, 15 ± 8% (p < 0.05). However, with partial inhibition (PAM, 3 ìM) only PGI2 +NO inhibited aggregation: vehicle, 67 ± 6%; PGI2, 56 ± 9%; NO, 62 ± 5%; PGI2 +NO, 33 ± 15%. Conclusion: We demonstrate that PGI2 and NO synergise with P2Y12 blockade to produce the greatest platelet inhibition and that platelet reactivity, despite DAPT is powerfully influenced by the presence of NO and PGI2 . This highlights that in vivo platelet reactivity will be a function of the level of P2Y12 receptor blockade and levels of extrinsic inhibitory endothelial mediators. This may be relevant to the efficacy of anti-platelet therapies in patients with endothelial dysfunction and introduces the concept of assessing endothelial function in patients undergoing ex vivo platelet function testing to help bridge the disconnect between results of platelet testing and thrombotic outcomes.